Sintesis Cepat Nanopartikel Perak dengan Irradiasi Gelombang Mikro dan Aplikasinya sebagai Antibakteri pada Kain Katun - Mohammad Alauhdin; Ahmad Dzulfiqar; Arsenius Olfa Herlistyawan (Jurnal Riset Kimia, 2022)
Silver nanoparticles (AgNPs) are silver metal particles with nanoscale size. In the scale, they generate different properties compared to the original particle or material. AgNPs can be synthesized in several ways, one of which is through chemical reduction. This method is accelerated by heating, usually using conventional heating. However, the heating takes time, so it is less effective for application. In this study, AgNPs were synthesized by chemical reduction with sodium citrate as a reducing agent accompanied by microwave irradiation to speed up the synthesis process. The resulting AgNPs were then applied to cotton fabric as an antibacterial agent. The reaction lasted for 6 minutes, much faster than using conventional heating. The synthesized particles have an average size of 56.2 nm and are stable for up to 41 days of storage. The AgNPs then can be applied to cotton fabric and inhibit the growth of S. aureus and P. aeruginosa bacteria with a Minimum Inhibitory Concentration of 70%.